Modeling and Simulation in Scilab/Scicos with ScicosLab 4.4 - Campbell, Stephen L.; Chancelier, Jean-Philippe.; Nikoukhah, Ramine; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
ScicosLab is a free open-source software package for scientific computation. It includes a Scilab interpreter and hundreds of general purpose and specialized functions for numerical computation, organized in libraries called toolboxes, which cover such areas as simulation, optimization, systems and control, and signal processing. One important ScicosLab toolbox is Scicos. Scicos provides a block diagram graphical editor for the construction and simulation of dynamical systems. The objective of this book is to provide a tutorial for the use of Scilab/Scicos with a special emphasis on modeling and simulation tools. The book is based on the new ScicosLab 4.4. While the book will provide useful information to experienced users it is designed to be accessible to beginning users from a variety of disciplines. Students and academic and industrial scientists and engineers should find it useful. The book is divided into two parts. The first part concerns Scilab and includes a tutorial covering the language features, the data structures and specialized functions for doing graphics, importing, exporting data and interfacing external routines. It also covers in detail the numerical solvers for ordinary differential equations and differential-algebraic equations available in ScicosLab. Even though the emphasis is placed on modeling and simulation applications, this part provides a global view of the Scilab language. The second part is dedicated to modeling and simulation of dynamical systems in Scicos. This type of modeling tool is widely used in industry because it provides a means for constructing modular and reusable models. This part contains a detailed description of the editor and its usage, which is illustrated through numerous examples. All codes used in the book are made available to the reader. This book is an updated and expanded version of an earlier edition based on Scilab 3.1. Stephen L. Campbell is a professor of mathematics and director of graduate programs at North Carolina State University, a fellow of the IEEE, and has published extensively on numerical methods and control. Jean-Philippe Chancelier is affiliated with CERMICS Ecole Nationale des Ponts et Chaussees and is one of the original developers of Scilab. Ramine Nikoukhah is a director of research at INRIA (The French National Institute for Research in Computer Science and Control), senior member of IEEE, one of the original developers of Scilab, and is the creator of Scicos.
1 Scilab -- General Information -- to Scilab -- Modeling and Simulation in Scilab -- Optimization -- Examples -- 2 Scicos -- Getting Started -- Scicos Formalism -- Scicos Blocks -- Examples and Applications -- Batch Processing in Scilab -- Code Generation -- Debugging -- Implicit Scicos and Modelica -- Inside Scicos -- Coding Examples.
Keywords: Mathematics; Computer simulation; Differentiable dynamical systems; Computer science -- Mathematics; Control engineering systems; Mathematics; Computational Mathematics and Numerical Analysis; Control , Robotics, Mechatronics; Dynamical Systems and Ergodic Theory; Operations Research/Decision Theory; Simulation and Modeling